Optimizing nano-nitrogen and conventional sulphur doses for enhanced growth and yield in sunflower (Helianthus annuus) - Guhan , M; Kalaiyarasan , C; Anandan, P; Elayaraja, D (The Indian Journal of Agricultural Sciences, 2026)
Field experiments were carried out to explore the influence of nano formulation of nitrogen and conventional sulphur on growth and yield of sunflower (Helianthus annuus L.) cultivated in heavy textured soil. The study was conducted during kharif (July to October, 2024) and rabi (January to April, 2025) seasons at the Experimental Farm, Department of Agronomy, Faculty of Agriculture, Annamalai University, Annamalai Nagar. The design followed was randomised block design involving 11 unique treatments, which were replicated thrice. The treatments comprised of four levels of nitrogen (30, 45, 60 and 90 kg/ha) through urea and nano urea and sulphur (45 kg/ha) through gypsum. Regarding the various treatments imposed in the experiments, T11 (45 kg nitrogen through urea + 45 kg nitrogen through nano urea + 45 kg sulphur per ha through gypsum) registered maximum values for growth and yield attributes, seed yield (2722 and 2613 kg/ha) and Stalk yield (4828 and 4634 kg/ha) of sunflower in both crop seasons. The lowest values for growth attributes, yield attributes and yield (seed and stalk) were observed under control treatment (T1) in both crop seasons. Experimental findings obtained from current investigation found that combined application of nano and conventional nitrogen and sulphur had a profound impact towards growth and yield attributes and yield of sunflower over control in both crop seasons.